The venom of South American rattlesnakes inhibits macrophage functions and is endowed with anti-inflammatory properties - Silva, Maria C. C. de Sousa e (Hindawi Publishing Corporation, 1996)
The injection of Crotalus durissus terrificus venom into the foot pad of mice did not induce a significant inflammatory response as evaluated by oedema formation, increased vascular permeability and cell migration. The subcutaneous injection of the venom, or its addition to cell cultures, had an inhibitory effect on the spreading and phagocytosis of resident macrophages, without affecting the viability of the cells. This effect was not observed when the venom was added to cultures of thioglycollate elicited macrophages, but it was able to inhibit these macrophage functions when the cells were obtained from animals injected simultaneously with the venom and thioglycollate. These observations suggest that the venom interferes with the mechanisms of macrophage activation. Leukocyte migration induced by intraperitoneal injection of thioglycollate was also inhibited by previous venom injection. This down-regulatory activity of the venom on macrophage functions could account for the mild inflammatory response observed in the site of the snake bite in Crotalus durissus terrificus envenomation in man.